CULTURAL COMPONENT OF PUBLIC DIPLOMACY IN THE DIMENSIONS OF ECONOMIC PROGRESS OF COUNTRIES - Хоменська, Інна; Запухляк, Віталій (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article deals with the issue of cultural diplomacy, which is investigated by national and foreign scholars but its impact on economic progress is not enough studied. It was proved that culture is a reason, which forms the image of the country and creates a positive profile for other countries. The trends of the global development and main risks are revealed, which will have long term character and influence economic progress. It was proved that the greatest risks are in ecological and social spheres. There is a violation of social cohesion. The need to bring countries closer to each other including communication platforms and cultural diplomacy was proved. The interest of the world community to Ukraine was explained. The role of the culture as a unique form of a dialogue and renewing of a multilateral cooperation and support of economic progress was identified. The essence of European policy in the area of cultural diplomacy was revealed. The strategy of international cultural relations was analyzed. Cultural values are connected with goals of the sustainable development. Correspondence of the UNESCO Convention in the field of culture with the objectives of the Sustainable Development Goals was carried out. To assess the contribution of the culture to the achievement of the Sustainable Development Goals, the UNESCO methodology was analyzed, which covers 22 indicators in 4 interdisciplinary thematic areas, which include the components of sustainable development and knowledge, and skills. The role of public diplomacy and the cultural component for Ukraine is clarified. The Public Diplomacy Strategy of the Ministry of Foreign Affairs of Ukraine for 2023-2025 is in force in Ukraine. This Strategy is designed to improve the image of Ukraine and promote the implementation of measures to promote the country. It is proved that Ukraine should use world practices to increase its visibility. Despite the written challenges and risks, some measures have been proposed that will turn cultural diplomacy (including that of Ukraine) into a driver of economic development of countries.